ANCAMAN JENIS IKAN ASING LOUHAN TERHADAP IKAN ENDEMIK DI DANAU MATANO, SULAWESI SELATAN - Nasution, Syahroma Husni; Haryani, Gadis Sri; Dina, Rahmi; Samir, Octavianto (BERITA BIOLOGI, 2019)
Lake Matano is one of the ancient lakes in Sulawesi where some endemic fish species of Telmatherina, Mugilogobius, Oryziasand Glossogobius matanensis lived. The presence of alien species can be on threat for the loss of biodiversity in fresh waters, including endemic fish in Lake Matano. The research aim to review the threat of louhan fish as alien species to endemic fish in Lake Matano. The study was conducted in Lake Matano at five stations in April and August 2015 namely Lawa, Nuha, Petea, Pantai Impian, and Pantai Kupu-kupu. Sam-ples were collected using experimental gillnet with mesh size of ¾; 1; 1¼; 1?2; 2; 2,5; and 3 inches. Fouteen species were found consist of 10 endemic species and red list.These were three of genus Glossogobius, seven species of Telmatherina, and four alien species of the carp (Cyprinus carpio), louhan, gourami (Trichopodus trichopterus), and tilapia (Oreochromis niloticus). The most common species of endemic fish is T. antoniae. Louhan is the result of a hybrid species Amphilopus citrinellus x Cichlasoma trimaculatum. The abundance of louhan is 64 in April and 40 fishes in August, respectively at a time caught. The percentage ratio of louhan to endemic fish was of 8.6% and 18.3%. This indicated that the louhan fish tend to be invasive and certainly threatened endemic fish survival in this lake. The maturity of gonads of louhan is in the level of I - IV that enables the fish to reproduce quickly.